2004
DOI: 10.1080/13576280310001656196
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Empathy to First Year Medical Students: Evaluation of an Elective Literature and Medicine Course

Abstract: A brief literature-based course can contribute to greater student empathy and appreciation for the value of humanities in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
158
0
15

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(178 citation statements)
references
References 26 publications
5
158
0
15
Order By: Relevance
“…Several methods of integrating humanities interventions were described. A common format was small group teaching, and interventions were often facilitated by a professional with humanities experience (George 2011, Wald 2010, Gulpinar 2009, Boudreau 2007, Wachtler 2006, Karnad 1999, Shapiro 2004, Hawkins 2003, Andre 2003, Shapiro 2003, Newell 2003, Anderson 2003. Only three interventions utilized newer methods of medical education such as websites to curate content, or social media to enable more frequent communication between students (Wiecha 2002, Wiecha 2008, George 2011.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods of integrating humanities interventions were described. A common format was small group teaching, and interventions were often facilitated by a professional with humanities experience (George 2011, Wald 2010, Gulpinar 2009, Boudreau 2007, Wachtler 2006, Karnad 1999, Shapiro 2004, Hawkins 2003, Andre 2003, Shapiro 2003, Newell 2003, Anderson 2003. Only three interventions utilized newer methods of medical education such as websites to curate content, or social media to enable more frequent communication between students (Wiecha 2002, Wiecha 2008, George 2011.…”
Section: Resultsmentioning
confidence: 99%
“…Only ten articles included any formal method of evaluation or assessment of impact beyond learner satisfaction. Of those ten articles, five used qualitative techniques to evaluate learners (Thompson 2015, Ramani 2013, Gulpinar 2009, Wachtler 2006, Bonebakker 2003, three used quantitative measures (Rodriguez 2013, Wiecha 2008, Wiecha 2002, and two used a combination (Shapiro 2004, Shapiro 2005. Quantitative measures were typically Likert scales or validated empathy scales (Empathy Construct Rating Scale and the Balanced Emotional Empathy Scale (Shapiro 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The female-brained student has a natural tendency to emotionally resonate with others, attuning them to subtle clues as to the patient's true feelings; the student who is extroverted in social orientation may more easily gain the patient's trust; the student with a disposition toward cognitive flexibility may be best at seeing the world from the perspective of the patient's values, beliefs and desires. Despite natural constraints on individual capacities to learn empathy-related skills, engagement in the humanities (Shapiro et al, 2004;Stepien & Baernstein, 2006) and training in patient-centred interviewing (Benbassat & Baumal, 2004;Stepien & Baernstein, 2006) are reportedly beneficial as means to promote the cognitive, affective and behavioural components of empathy amongst medical students.…”
Section: What Should We Do About Empathy Then?mentioning
confidence: 99%
“…More recently, this condemnation reached a climax when objective studies confirmed that empathy amongst medical students and residents declines as they progress throughout their training (Newton et al, 2000;Spencer, 2004;Hojat et al, 2004). By consequence, an extensive literature has emerged on the questions of how physicians should be empathic (Halpern, 2003;Benbassat & Baumal, 2004;Larson & Yao, 2007), how it should be measured (Hojat et al, 2004;Stepien & Baernstein, 2006), and how best to "educate" empathic physicians (Shapiro et al, 2004;Platt & Keller, 1994;Burack et al, 1999;Winefield & Chur-Hansen, 2000). Evidently, empathy in medicine is very much on the radar today.…”
Section: Introductionmentioning
confidence: 99%
“…Another is empathy (AAMC 2005), and research suggests that engagement with literature promotes medical students' ability to empathize with patients (McLellan and Jones 1996). Confronting complicated human behavior through literary texts has, along with reflective writing and perspective taking, been associated with patient-centeredness (Blatt et al 2010), increased self-awareness, and empathy among providers (DasGupta and Charon 2004;Shapiro et al 2004). Theory of mind research by Kidd and Castano (2013) links empathy to engagement with characters whose Binner lives are rarely easily discerned but warrant exploration^(378).…”
mentioning
confidence: 99%